Biochemical Analyses of Male Rat’s Serum Administered Dexamethasone and Green Synthesis Cerium Oxide Nanoparticles Treatment - Ruaa M. Ali1, Nada K. Abbas1, Amal K. Abbas2, Lamia K. Abbas3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Current research involves preparing cerium oxide nanoparticles using simple, environmental- friendly green synthesis approach via fresh green tea leaf extract (Camellia sinensis) as a capping and reducing agent, Ultraviolet-visible spectroscopy (UV-Vis.) is used to check the formation of nanoparticles by investigate the absorption peak and energy gap (Eg); Maximum absorption peak was around 295nm and Eg was 4.2eV calculated using Planck’s equation, X-Ray diffraction (XRD) analysis of Nano powder stated that Cerium Oxide has a cubic fluorite structure with face centered cubic (FCC) structure, blood serum glucose levels, liver functions after CeO2 Nanoparticles treatment for rats were reported in this paper. Forty eight adult male rats were used and divided randomly into six groups each group has eight rats (n=8), Results stated that blood glucose levels, liver enzymes were increased in groups that injected by dexamethasone while considerably modified in rats administered by Cerium Oxide Nanoparticles.